Challenging the national border system through love in César Mba A. Abogo’s “The Thickness of the Night” and Lien Carrazana’s “An Expatriate Waitress, Anywhere in the World” (Castilla. Estudios de Literatura, 2022)
The short stories “En la espesura de la noche” (2010) and “Una camarera (expatriada a cualquier lugar del mundo)” (2011) depict the feeling of imprisonment that first-person narrators experience within the rigid borders of Equatorial Guinea and Cuba, respectively, and how they overcome this territorial oppression by loving a woman who dwells beyond the national borders they are unable to trespass. Bearing in mind that the love towards nation-states constitutes a way of perpetuating a nationalist ideology and the reinforcement of national borders over individual free agency (Morrison et al., 2021: 514), this article examines how, in both narratives, the exaltation of a transnational love over that of the nation challenges these nation-state’s “unique discourse,” based on the binary border thinking of inside/outside and us/them, in favor of individual agency and a more transnational way of understanding the world.
Keywords: national borders; Cuba; Equatorial Guinea; transnational love